Mesoscale modelling of concrete reinforced with spiral steel fibres under dynamic splitting tension - Hao, Yifei; Huang, X.; Hao, Hong (SAGE PUBLICATIONS INC, 2018)
© 2017, © The Author(s) 2017. The addition of discrete steel fibres into concrete has been widely recognised as an effective measure to enhance the ductility, post-cracking resistance and energy absorption of the matrix subjected to impact loads. Despite useful information from experimental studies that investigate the macro-scale performance of steel fibre–reinforced concrete under dynamically applied loadings, results from a series of tests or from tests by different researchers are often found to be scattered. Besides variations in testing conditions, random var iations of size, location and orientation of aggregates and fibres in steel fibre–reinforced concrete are deemed the fundamental reason of the scattering test data. High-fidelity modelling of concrete and steel fibre–reinforced concrete in mesoscale has been widely adopted to understand the influence of each component in the composite material. Numerical studies have been published to discuss the behaviour of steel fibre–reinforced concrete under dynamic splitting tension. Different shapes, for example, circles, ovals and polygons, of coarse aggregates were considered in different studies, and different conclusions were drawn. This study investigates the influence of the shape of aggregates on numerical prediction in mesoscale modelling of steel fibre–reinforced concrete materials with spiral fibres under dynamic splitting tension in terms of the strain distribution, cracking pattern and strength. The numerical model is validated by experimental results. It is found that the shape of aggregates in mesoscale modelling of splitting tensile tests has negligible influence. Furthermore, steel fibre–reinforced concrete specimens with different volume fractions of spiral fibres from 0.5% to 3.0% under various loading rates are simulated. Results from parametric simulations indicate the optimal dosage of spiral fibres in steel fibre–reinforced concrete mix with respect to the construction cost and mechanical property control.